A modelling-based economic evaluation of primary-care-based fall-risk screening followed by fall-prevention intervention: a cohort-based Markov model stratified by older age groups. (11th November 2019) - Franklin, Matthew; Hunter, Rachael Maree
Abstract: Background: fall-risk assessment with fall-prevention intervention referral for at-risk groups to avoid falls could be cost-effective from a care-payer perspective. Aims: to model the cost-effectiveness of a fall-risk assessment (QTUG compared to TUG) with referral to one of four fall-prevention interventions (Otago, FaME, Tai Chi, home safety assessment and modification) compared to no care pathway, when the decision to screen is based on older age in a primary care setting for community-dwelling people. Methods: a cohort-based, decision analytic Markov model was stratified by five age groupings (65–70, 70–75, 65–89, 70–89 and 75–89) to estimate cost per quality-adjusted life years (QALYs). Costs included fall-risk assessment, fall-prevention intervention and downstream resource use (e.g. inpatient and care home admission). Uncertainty was explored using univariate, bivariate and probabilistic sensitivity analyses. Results: screening with QTUG dominates (>QALYs; <costs) screening with TUG irrespective of subsequent fall-prevention intervention. The QTUG-based care pathways relative to no care pathway have a high probability of cost-effectiveness in those aged 75–89 (>85%), relative to those aged 70–74 ( 10 < 30%) or 65–69 (<10%). In the older age group, only a 10% referral uptake is required for the QTUG with FaME or Otago modelled care pathways to remain cost-effective. Conclusion: the highest probability of cost-effectiveness observed was a care pathway incorporating QTUG with FaME in those aged 75–89. Although the model does not fully represent current NICE Falls guidance, decision makers should still give careful consideration to implementing the aforementioned care pathway due to the modelled high probability of cost-effectiveness.